Kesiapan Guru Sekolah Dasar untuk Menerapkan Pembelajaran Terdiferensiasi: Korelasi dengan Efikasi Diri dan Sikap Guru - Dwi Rohmiyati Khasanah; Agung Hastomo; Fery Muhammad Firdaus (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
In the context of contemporary education, differentiated learning is a crucial strategy for accommodating students' diverse readiness levels, interests, and learning styles. Successful implementation of this strategy depends heavily on teachers' readiness, including their conceptual understanding, self-efficacy, and attitude toward pedagogical change. This study evaluates elementary school teachers' readiness to implement differentiated learning, focusing on self-efficacy and attitudes toward the approach. Using a descriptive correlational design, data were collected via questionnaires from teachers who had attended related training. The results of the analysis show a significant positive relationship between teachers' self-efficacy and attitudes and their readiness to implement differentiated learning; teachers who are confident and positive tend to adopt this approach more often. However, system limitations and classroom management challenges remain the main barriers. These findings underscore the importance of professional development programs that enhance teachers' knowledge, self-efficacy, and attitudes. This provides policymakers with practical implications for supporting inclusive and adaptive teaching strategies to improve learning quality.